PARALLEL GRAFT TECHNIQUE: UMA ALTERNATIVA PARA O TRATAMENTO DE PATOLOGIA DO ARCO AÓRTICO - Augusto, Rita (2020)
Treatment of aortic pathologies involving the aortic arch represents a great challenge for vascular surgeons. Endografting techniques, comparing to open surgery, are less invasive approaches. However, an adequate proximal landing zone remains a challenge and, regarding this issue, parallel graft techniques represent a viable endovascular treatment option in patients with challenging aortic arch pathology by extending the proximal landing zone while maintaining aortic side branches perfusion. Parallel graft techniques required a thorough planning and the clinical and imagiological follow-up are mandatory. They appear to be a safe and minimally invasive alternative techniques in selected fragile patients. The authors report three clinical cases that required the use for parallel grafts to treat complex pathology of aortic arch.